Land Policy Issues in Nepalese Context - Subedi, Gandhi; Chhatkuli, Raja Ram (Journal on Geoinformatics, Nepal, 2010)
The land issues comprise all social, economical and legal measures that determine the access to land and allocation of land related benefits. Land administration plays important role in obtaining national political objectives by operating land policy instruments properly. This paper aims to discuss various land policy issues in Nepal. The literature regarding land policy and land administration, concerning laws and reports are reviewed. The concept and definition of land policy and land administration and their relationship is provided first; and then the land policy issues and major challenges are discussed, some measures to overcome such challenges are also presented; and conclusion is drawn from the whole study. Lack of national land policy and land use policy, no guarantee of registered deed, lack of fair compensation in case of expropriation, lack of clear government policy to regulate land market, improper land valuation system, traditional, complex and cumbersome procedure, lack of coordination between land administration organizations, poor management of land records, manual recording system, lack of one stop shopping, difficult to retrieve land information, lack of skilled manpower, misuse of public land, lack of national policy to provide land to the landless and poor people and protection of rights of the indigeneous people are the major problems identified from the study. Formulation of national land policy and land use policy addressing all land issues, improvement in registration system, simplification of procedures, integration of land administration organizations, digitization of land records, establishment of National Spatial Data Infrastructure, providing online services and hiring trained manpower/providing training to existing manpower are some of the measures for improvement in the existing land administration system of Nepal.